Zmiany wybranych wskaźników i cech gazometrii krwi w okresie fizjologicznej restytucji po wysiłku wytrzymałościowym mężczyzny w 6 dekadzie życia. Opis przypadku - Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2015)
Mrozkowiak Mirosław. Zmiany wybranych wskaźników i cech gazometrii krwi w okresie fizjologicznej restytucji po wysiłku wytrzymałościowym mężczyzny w 6 dekadzie życia. Opis przypadku = Changes in selected indicators and characteristics of blood gases during the period of physiological restitution after exercise endurance man in the 6 decade of life. A case report. Journal of Education, Health and Sport. 2015;5(7):489-506. ISSN 2391-8306. DOI 10.5281/zenodo.21437 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A489-506 https://pbn.nauka.gov.pl/works/594545 http://dx.doi.org/10.5281/zenodo.21437 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. Zmiany wybranych wskaźników i cech gazometrii krwi w okresie fizjologicznej restytucji po wysiłku wytrzymałościowym mężczyzny w 6 dekadzie życia. Opis przypadku Changes in selected indicators and characteristics of blood gases during the period of physiological restitution after exercise endurance man in the 6 decade of life. A case report Mirosław Mrozkowiak Uniwersytet Kazimierza Wielkiego, Instytut Kultury Fizycznej Zdrowia i Turystyki, ul. Ogińskiego 16, Bydgoszcz Słowa kluczowe: wysiłek wytrzymałościowy, wczesna i późna samoistna restytucja. Keywords: exercise endurance, early and late spontaneous restitution. Streszczenie Wprowadzenie. Wypoczynek rozumieniu fizjologicznym jest dynamicznie zmiennym stanem ustroju, następującym bezpośrednio po zakończeniu bądź też zmniejszeniu intensywności wysiłku fizycznego lub umysłowego. W tym okresie dominują procesy asymilacyjne nad dysymilacyjnymi. Spadek wydolności fizycznej w starszym wieku należy tłumaczyć pogorszeniem stopnia perfuzji mięśni podczas wysiłku. Jego przyczyn należy upatrywać w anatomicznych zmianach zachodzących zarówno w mięśniu sercowym, jak i w naczyniach krwionośnych. Celem pracy jest wykazanie zmian wybranych wskaźników i cech gazometrii krwi w okresie fizjologicznej restytucji po wysiłku wytrzymałościowym u mężczyzny w 6 dekadzie życia. Materiał i metody. Badany mężczyzna realizujący zdrowy styl życia poddał się oznaczeniu wybranych wskaźników krwi po wysiłku wytrzymałościowym w czasie restytucji samoistnej: pH, PCO2, PO2, BB, BE, BEart,cHCO3, SO2(c). Uzyskane wyniki. Pozytywne wyniki zaobserwowano w większości mierzonych wskaźników i cech gazometrii krwi. Przy czym różnie prezentowała się ich konfiguracja w trakcie 5 dniowego cyklu pomiarowego. Najbardziej pozytywne zmiany zaobserwowano w wielkości: BB, BE, PCO2. Wnioski W okresie wczesnej restytucji po wysiłku wytrzymałościowym u 61 letniego mężczyzny normalizacji ulega: ciśnienie skurczowe i rozkurczowe krwi, tętno, ciśnienie parcjalne dwutlenku węgla, zasady buforujące osocze, stan zasad (nadmiar / niedobór). W okresie restytucji późnej: saturacja tlenowa, ciśnienie parcjalne tlenu. Należy przyjąć, że wskaźnik aktualnego nadmiaru zasad i stężenia jonów wodorowęglanowych wymaga dłuższego okresu normalizacji niż 54 godzina restytucji późnej. Abstract Introduction. Rest meaning is dynamically variable physiological state of the body, immediately following the completion or reducing the intensity of physical or mental. During this period, dominated by the processes of assimilation over dissimilation. The decline of physical performance in older extent be explained by the deterioration of muscle perfusion during exercise. Its causes should be sought in anatomical changes occurring both in the myocardium, as well as blood vessels. The aim of the study is to demonstrate the changes in selected indicators and characteristics of blood gases during the period of physiological restitution after exercise endurance for a man in 6 decade of life. Materials and methods. Tested man pursuing a healthy lifestyle surrendered to the designation of selected indicators of blood after exercise endurance during spontaneous restitution pH, PCO2, PO2, BB, BE, BEart,cHCO3, SO2(c). Obtained results. Positive results were observed in most measured rates and characteristics of blood gases. At the same time differently they presented their configuration during the 5-day measurement cycle. The most positive changes were observed in the size of BB, BE, PCO2. Conclusions 1. During the early restitution after exercise endurance in a 61 year old male normalization is: systolic and diastolic arterial blood pressure, heart rate, the partial pressure of carbon dioxide, the principle of buffering plasma, state principles (excess / deficiency). In the late restitution: oxygen saturation, partial pressure of oxygen. 2. It is assumed that the current rate of excess bases and bicarbonate ion concentration requires a longer period of normalization than 54 hours restitution of late.